Economics of East Coast fever: a literature review - Surve, Aditi A.; Hwang, Jae Young; Manian, Shanthi; Onono, Joshua Orungo; Yoder, Jonathan (Frontiers in Veterinary Science, 2023)
East Coast fever (ECF) is a cattle disease caused by a protozoan parasite called Theileria parva (T. parva). Theileria parva is transmitted among cattle by ticks. It is endemic in parts of central, eastern, and southern Africa and imposes an economic burden through illness and death of approximately a half of a billion U.S. dollars annually. This paper reviews existing science on the economics of ECF. We utilize a conceptual model that defines primary categories of economic costs due to ECF and use it to organize a synthesis of the literature on aggregate and micro level direct costs of the disease and the costs and benefits related to various ECF management strategies. We then identify knowledge gaps to motivate for future research.